Waste and Circular Economy - Senatore, Gianluca; Teofili, Simone (Richtmann Publishing, 2021)
This work aims to describe and analyze the new socio economic phenomenon of waste-based circularity. To describe this process of recovery and transformation of waste, which represents the basis of circular economy, it is necessary to understand the complex articulation of the production of goods and materials, their yield and their capacity of transformation. At the heart of all this is a series of human behaviors and habits dictated by legal rules and economic and cultural approaches. If we manage to better understand these behaviors, we can activate a series of processes which could help us to determine and encourage more sustainable behaviors from an environmental, economic and social point of view. Received: 11 March 2021 / Accepted: 18 April 2021 / Published: 17 May 2021